Investigating the impact of Multiwalled Carbon Nanotubes exposure on enzymatic activities and histopathological variations in Swiss albino mice - Iqra Nasim; Nadia Ghani; Rab Nawaz; Emilio Mateev; Yousef A. Bin Jardan (Scientific Reports)
Abstract Present study was conducted to evaluate the detrimental impacts of exposure of Multi-walled Carbon Nanotubes (MWCNT-NP) on enzymatic activities and tissue structures in Swiss albino mice. The experimental groups of mice received MWCNT-NP for specific time period (seven or fourteen days). Two distinct doses of the MWCNT-NP solution were given orally: 0.45 µg and 0.90 µg, and the distilled water was given to the control group. Serum samples were extracted at 7 and 14 days after the experiment by centrifuging whole blood for 15 min at 3,000 rpm. An enzyme-linked immunosorbent test (ELISA) was used to measure many enzyme assays, such as Angiotensin Converting Enzymes (ACE), Alanine Aminotransferase (ALT), Aspartate Aminotransferase (AST), and Nicotinamide Adenine Dinucleotide Phosphate (NADPH) oxidase enzyme. Hematoxylin and Eosin (H&E) staining of tissue samples was done along with a histopathological examination. During a 14-day exposure, ACE, NADPH Oxidase, ALT, and AST enzyme levels were significantly higher in the exposed groups (0.45 µg and 0.90 µg) than in the control group (p < 0.05). Male mice exposed to MWCNT-NP showed substantial histological damage in the relevant organs as well as elevated enzyme activity levels. Present study showed a comprehensive and practical assessment of the toxicity associated with MWCNT-NP of different geometries and functionalization.